Knowledge Sharing and Employee Performance: the mediating role of Organizational Learning - Bayu Setyo Nugroho; Hadiahti - Utami; Mellasanti - Ayuwardani; Nanang Adie Setyawan (Admisi dan Bisnis, 2022)
This study aims to obtain the latest insights on various issues of Knowledge sharing and Organizational Learning variables to increase Employee Performance of SMEs. The sample was obtained through purposive sampling technique as many as 101 respondents spread over various areas in Semarang. The research technique uses Structural Equation Modeling (SEM) through the Partial Least Square (PLS) program. Other variables obtained from 101 respondents are name, age, gender, last education, SME identity, age when SMEs have operated, and domicile address. Filling out this questionnaire will take at least 20 minutes. The age range varies from less than 30 years old to a maximum age of 50 years. 85% who participated in this questionnaire were women, while the remaining 15% were men. Educational Background 40% are Bachelors and diplomas from universities, while the rest have equivalent high school backgrounds. The results of the study can explain the positive effect of the Knowledge Sharing variable on the increase in Organizational Learning by 41.9%, and the positive influence of the Knowledge Sharing variable on the increase in Employee Performance by 55.8%, and both have P-values < 0.05, namely 0.000 and 0.012. Knowledge Sharing (KS) has a positive effect on Employee Performance (EP) through Organizational Learning (OL) mediation, the significance of which is 0.000 or <0.05 with a quasi-mediating